Cbl Associates with Pyk2 and Src to Regulate Src Kinase Activity, α(v)β(3) Integrin-Mediated Signaling, Cell Adhesion, and Osteoclast Motility - Sanjay, Archana (The Rockefeller University Press, 2001)
The signaling events downstream of integrins that regulate cell attachment and motility are only partially understood. Using osteoclasts and transfected 293 cells, we find that a molecular complex comprising Src, Pyk2, and Cbl functions to regulate cell adhesion and motility. The activation of integrin α(v)β(3) induces the [Ca(2+)](i)-dependent phosphorylation of Pyk2 Y402, its association with Src SH2, Src activation, and the Src SH3-dependent recruitment and phosphorylation of c-Cbl. Furthermore, the PTB domain of Cbl is shown to bind to phosphorylated Tyr-416 in the activation loop of Src, the autophosphorylation site of Src, inhibiting Src kinase activity and integrin-mediated adhesion. Finally, we show that deletion of c Src or c-Cbl leads to a decrease in osteoclast migration. Thus, binding of α(v)β(3) integrin induces the formation of a Pyk2/Src/Cbl complex in which Cbl is a key regulator of Src kinase activity and of cell adhesion and migration. These findings may explain the osteopetrotic phenotype in the Src(−/)− mice.